2011
DOI: 10.1210/me.2011-1024
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of GSTP1, a Prostate Cancer Prognostic Gene, by the Estrogen Receptor-β and Endothelial Nitric Oxide Synthase Complex

Abstract: We recently identified in prostate tumors (PCa) a transcriptional prognostic signature comprising a significant number of genes differentially regulated in patients with worse clinical outcome. Induction of up-regulated genes was due to chromatin remodeling by a combinatorial complex between estrogen receptor (ER)-␤ and endothelial nitric oxide synthase (eNOS). Here we show that this complex can also repress transcription of prognostic genes that are down-regulated in PCa, such as the glutathione transferase g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 51 publications
8
26
0
Order By: Relevance
“…In current study statistically significant downregulation of GSTP1 was observed in brain tumor samples compared to control samples. Similar results have also been observed in breast cancer (Erlap et al, 2013), prostate cancer (Okino et al, 2007;Re et al, 2011) and colon cancer (Ritchie et al, 2009).Whereas conflicting results for GSTP1 expression pattern have been reported in some of other studies (Masood et al, 2011;Uchida et al, 2013). In present study, significant down-regulation of GSTP1 was observed in more advance grade of brain tumor samples when compared with early grade of brain tumor.…”
Section: Discussionsupporting
confidence: 88%
“…In current study statistically significant downregulation of GSTP1 was observed in brain tumor samples compared to control samples. Similar results have also been observed in breast cancer (Erlap et al, 2013), prostate cancer (Okino et al, 2007;Re et al, 2011) and colon cancer (Ritchie et al, 2009).Whereas conflicting results for GSTP1 expression pattern have been reported in some of other studies (Masood et al, 2011;Uchida et al, 2013). In present study, significant down-regulation of GSTP1 was observed in more advance grade of brain tumor samples when compared with early grade of brain tumor.…”
Section: Discussionsupporting
confidence: 88%
“…As reported in previous studies from our group, in response to estrogenic stimuli, eNOS and ERs form nuclear complexes that modulate gene transcription in HUVEC and prostate cancer cell lines6181923. Validation of the eNOS peaks within HOTAIR and MALAT1 regulatory regions as emerged by ChIP-Seq was confirmed by traditional ChIP in HUVEC, C27IM, and LNCaP cells in independent experiments (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Of note, responsiveness to ERβ selective ligand, 3βAdiol, was abrogated by both HOTAIR and MALAT1 knockdown (Supplementary Fig. S4), indicating that both lncRNAs are necessary to achieve a complete estrogen responsiveness upon treatment with this androgen metabolite capable to selectively bind ERβ2331. Similarly, an abrogation of pS2 estrogen sensitivity was observed by interference of MALAT1 (efficiency about 80%, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Data analysis was conducted following the instructions of the SABiosciences Web site (http://www .sabiosciences.com/methylationdataanalysis.php). DNA for the methyl-DNA immunoprecipitation (MeDIp) assay was prepared from cross-linked chromatin, as previously described (15). Purified DNA (500-800 ng) was denatured and methylation analysis performed with MeDIP kit (Active Motif), according the manufacturer's instructions, using a specific monoclonal antibody to 5-methylcytosine or mouse IgG as the negative control.…”
Section: Dna Methylation Profiler and Methyl-dna Immunoprecipitation mentioning
confidence: 99%